Creencias en la comprensión de textos escritos en inglés en estudiantes de cuarto grado de secundaria en instituciones educativas públicas de Iquitos 2021 - Pezo Silva, Jean Piero Charsser (2023)
The aim of this study was to explain the influence of fourth year students’ beliefs in English reading at public secondary schools of Iquitos district, Perú. The investigation type was explanatory with field study, transecctional contemporary and multivariate designs. The study population was made up by 1656 with a stratified sample with proportional allocation of 312. Results show that the mean score in beliefs variable was 58,071 in a scale transformed to 100. Further, 196 students (62,8%) showed midly empowering beliefs. In reading comprehension, 11,53 was obtained as mean score in a scale out of 20, besides 154 students (49,4%) were ‘in process’ level of performance. Results of the binary logistic regression test was B= ,006 with p-value = ,002, and a causality index of 0,42, (42%). In conclusion, students’ beliefs influence in English reading comprehension. That is, the higher empowering beliefs, the higher reading comprehension.